A graphic history of sport : an illustrated chronicle of the greatest wins, misses, and matchups from the games we love - Janik, Andrew (New York : Clarkson Potter/Publishers, 2016)
A guide to the best moments in sports includes classic matchups, like Clay vs. Liston, backgrounds on such legendary coaches as Tom Landry, and information on great athletes represented with iconic imagery, like Flo Jo's colorful nails.
Includes index.
Keywords: Sports -- Miscellanea; Sports -- History